'Irrational Nuances': Interpreting Stockhausen's Klavierstück I. Issue 1 (February 2022) - JONES, GABRIEL
Abstract: The performance practice of European serial music has long been misunderstood. This article uses Stockhausen's Klavierstück I (1952–3) as a lens through which to view the realities of this practice, drawing on close contextual analysis of the affordances of the score and the now significant corpus of recordings. These findings are used to extend M. J. Grant's view of serial aesthetics and to provide a practical basis for what she calls 'serial listening'. Three principal styles of performance are identified and attendant modes of listening suggested, relating to the non-thematic principles and hermeneutic contexts of serial music, which include the embodied response of the performer to defamiliarized musical material and the nascent dialectic of instrumental and electronic composition. This investigation – informing serious judgements of value and taste – has broader implications for the development of Stockhausen's notation and temporal theory in the 1950s and for the performance practice of new music.